The Influence of the Three-Step Interview Technique on Students’ Speaking Skill - Devo, Oktaviano; Susilawati, Endang; Fajar Rahmani, Eka (Institut Agama Islam Negeri Palopo, 2024)
The capability to speak English is the prime key to being able to master English. Based on an interview between the researchers and the English teacher at school, students could not speak English with their peers or with their English teachers in daily context. Therefore, the researchers offered an alternative technique to aid English instructors by offering a responsive teaching-learning technique, which is the three-step interview technique. The objective of this research was to examine the impact of implementing the three-step interview approach on the speaking proficiency of tenth-grade students at SMA Negeri 1 Seberuang. The present study used a pre-experimental research approach, specifically using a one-group pre-test and post-test design. The sample was obtained using a cluster random sampling technique, resulting in a sample of 30 students in the X Mia class. The data were gathered from the outcomes of a pre-test and post-test and analyzed using a t-test and effect size calculation. The outcome of the t-test yielded a value of 5.45. The t-table value at a significance level of 0.05 and a degree of freedom (df) of 29 was determined to be 2.04. The data presented indicates that the t-test value (5.45) exceeded the critical value from the t-table (2.04). The results indicate that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The findings also indicat that the impact size score is 0.92, which falls within the moderate effect category. Based on the results, it can be inferred that the three-step interview approach has positive outcomes in enhancing the speaking proficiency of tenth-grade students at SMA Negeri 1 Seberuang.